Optimization of extraction process of plant-based gelatin replacer - Jaswir I.; Alotaibi A.; Jamal P.; Octavianti F.; Lestari W.; Hendri R.; Alkahtani H. (Universiti Putra Malaysia, 2024)
Indexed by WOS/ Scopus